Static Charged Fluid Spheres in General Relativity: Solutions of Einstein-Maxwell Field Equations with a Radical Metric Potential (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper provides solution of Einstein-Maxwell field equations for static spherically symmetric metric by using a seditious choice of metric potential and (ie. and The central and boundary conditions have been also discussed.